2017
DOI: 10.3382/ps/pex187
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in avian egg science: A review

Abstract: Eggs and egg products form an integral part of the food chain. As such, research into egg structure, function, and production has made an important contribution to the field of poultry science. The past decade has seen significant advances in avian egg science research, with work supplementing our understanding of the nature of the avian egg, and its biological, chemical, and physical properties. Eggshell color, strength, and chemical composition, poultry nutrition, and genetics have all been intensively studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 61 publications
1
33
0
2
Order By: Relevance
“…However, Kostogrys et al [33] did not find changes in a*, but they found L* and b* varied, when pomegranate seed oil was incorporated into the diet of Isa Brown hens. Other similar findings have also been reported to corroborate that both a bird's diet and breed determine the color of both the egg and its shell [34,35].…”
Section: Effect Of Breed and Diet Type On Egg Color Parameterssupporting
confidence: 67%
“…However, Kostogrys et al [33] did not find changes in a*, but they found L* and b* varied, when pomegranate seed oil was incorporated into the diet of Isa Brown hens. Other similar findings have also been reported to corroborate that both a bird's diet and breed determine the color of both the egg and its shell [34,35].…”
Section: Effect Of Breed and Diet Type On Egg Color Parameterssupporting
confidence: 67%
“…However, inorganic Zn replaced by organic Zn should be further investigated from every aspect. In addition, a substantial number of questions remain in fully understanding the avian eggshell quality; the precise chemical formation of the crystalline structure of the eggshell, the distribution of pores and processes behind termination of calcification all remain relatively unknown (51) and need to be further analysed.…”
Section: Discussionmentioning
confidence: 99%
“…It consists of a series of proteins [15][16][17] and of pigments responsible for the color of the shell. The brown shells contain cyclic tetrapyrrole derivatives [18,19] with the main representative protoporphyrin IX (PPIX), the free base (metal-free) version of heme. The green and blue-green shells contain biliverdin (BV), [20,21] an oxidative ring opening product of PPIX with broad absorption in the blue and orange-red region.…”
Section: Introductionmentioning
confidence: 99%